APPLICATION OF MUHAFADZOH NADHOM METHOD OF HIDAYATUS SHIBYAN IN IMPROVING QURAN READING SKILLS AT MI - Nadlir, Nadlir; Fitria, Sufatul; Zunita, Lucki (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2023)
This study aims to determine: 1) the implementation of the Hidayatus Shibyan Muhafadzoh method for students and 2). Application of the Hidayatus Shibyan Muhafadzoh method in improving students' reading skills. This research is a type of qualitative research with a case study model. Data collection techniques using interviews, observation, questionnaires, and documentation. The data analysis technique uses the Miles and Huberman model with the stages of data reduction, data presentation, and conclusion. This research was conducted at MI Al Rosyid Bojonegoro with a population of 165 students and 34 students in class 3 as a sample. The results of this study indicate that learning the Koran using the Hidayatus Shibyan Book Muhafadzoh method to improve students' reading skills is well implemented. The application of the Muhafadzoh Hidayatus Shibyan MI Al Rosyid method is by 1. Murojaah nadhom before class begins. 2. The teacher gives several questions to several students 3. The teacher explains the material associated with the Koran, 4. The teacher gives assignments to students and gives limits on the verses that will be memorized and before the lesson ends, the teacher gives reinforcement to students. With learning like this, students' reading skills of the Koran are increasing day by day. So that the Muhafadzoh method of Hidayatus Shibyan's book is categorized as being able to improve students' reading skills.